Tinjauan Kriminologis Tindak Pidana Perdagangan Orang di Kabupaten Ende - Matheus Paulino Mude Kiok; Thelma S.M. Kadja; Rosalind Angel Fanggi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to find out and analyze the criminological review of the crime of trafficking in persons studied in Ende Regency The type of research used in the study is empirical juridical research. Empirical Juridical Research, where prospective researchers conduct research in the field. Data collection technique by conducting interviews with 3 resource persons. As well as the data analysis techniques used, namely descriptive-qualitative analysis. The results of this study show that: (1) The factors that cause the occurrence of trafficking in Ende Regency. Namely, (a) Financial emotional pressure, (b) Lack of legal and moral awareness, (c) Poverty and economic inequality, (d) Lack of education and employment opportunities, (e) social and cultural, (f) family. (2) Efforts to combat trafficking in Ende Regency. In an effort to overcome trafficking in Ende Regency through 3 efforts, Preemptive, Preventive, and Repressive.